SISTEM KONSULASI PENYAKIT KULIT PADA DOMBA MENGGUNAKAN METODE NAÏVE BAYES - Dudi Muharam (JSIK (Jurnal Sistem Informasi Kaputama), 2020)
Sheep is a grazing animal. In raising sheep, sheep breeders on average have less knowledge in terms of skin diseases that attack their domestic sheep. Consultation system of skin diseases in sheep is used to help an expert or expert in diagnosing diseases in sheep based on existing symptoms. The purpose and benefits of consulting skin diseases in sheep, among others, is to facilitate and speed up knowing the types of skin diseases that attack sheep. To find out sheep disease, researchers made a consultation system by applying the naïve bayes method. Consultation of skin diseases in sheep using the Naïve Bayes method. In this study the type of skin disease that can be diagnosed as many as 5 diseases. with an accuracy rate of 100%. The conclusion of the research that has been done based on the problems that have been resolved through the creation of this consultation system is a consultation system to determine skin diseases in sheep designed by the naïve Bayes method.